The nexus between economic growth, urbanization, technological advancement, and CO2 emissions: Where does the GCC stand? - Bousrih, Jihen (Asian Journal of Economic Modelling, 2024)
Most countries, particularly developing and growing economies, have the primary goal of achieving greater economic growth in order to improve living standards. However, a boost in economic activity raises energy demand, which in turn raises carbon dioxide emissions and deteriorates the environment. This paper investigates the effect of economic growth, energy consumption, and research and development on CO2 emissions in Gulf Council Cooperation (GCC) countries. The study uses the Vector Error Correction Model to investigate the short- and long-run synergy between variables over the period 2000–2022. The results indicate that boosting economic activity requires more energy consumption and will increase CO2 emissions in the long run. Investing in research and development can enhance the quality of the environment, yet the effect of urbanization on CO2 emissions in GCC countries remains unclear. To reduce energy consumption, it is first necessary to expand renewable energy sources and encourage energy-saving techniques. Then, to lower CO2 emissions, the government must promote investments in green technologies, particularly in manufacturing. Third, the government should encourage sustainable urbanization by putting laws in place that encourage the growth of green cities and transportation networks.